Strategi Guru PAI dalam Mendesain Pembelajaran Aktif dalam Materi Pemulasaran Jenazah - Selly Saadatinnisa; Vellina Azzahra; Ahmad Alfarel; Bakti Fatwa Anbiya (Almeera Education, 2024)
This research is motivated by the low interest of students in the material of the funeral procession, which is often considered scary and less interesting. This perception causes students to be reluctant to delve into the material, so their understanding of important practices in religion becomes limited. In fact, this material has high educational and spiritual value, but the scary impression reduces students' enthusiasm to learn it. This is a challenge for teachers in delivering effective and easy-to-understand learning. This study aims to analyze the strategies used by PAI teachers in designing active learning on funeral materials, in order to improve students' understanding and skills in religious practices. The approach used in this study is qualitative with a literature method, namely analyzing various relevant literature. The data collection technique was carried out through a literature review. The results of the study show that the active learning strategies applied by teachers are effective in attracting students' interest. With this strategy, students can more easily understand and absorb the material being taught.